Retrospective study on Bethesda Ⅴ thyroid nodule in diagnosis of papillary thyroid carcinoma: retrospective study - YAN Shouyi, CHEN Hongbin, ZHANG Liyong, WANG Bo, CAI Shaojun, LIN Siying, ZHAO Wenxin (Waike lilun yu shijian, 2021)
Objective To study on preoperative diagnosis of papillary thyroid carcinoma (PTC) with Bethesda Ⅴ thyroid nodules retrospectively and to explore the differences of clinical parameters between Bethesda Ⅴ and Ⅵ thyroid nodules. Methods The clinical data of 430 patients were analyzed. Results Univariate analysis showed that there were significant differences of Bethesda Ⅴ nodules in nodule boundary, tumor size and echo between PTC group of 159 cases and benign group of 20 cases (P<0.05). It was shown from multivariate analysis that nodule boundary, tumor size and echo were risk factors for malignant diagnosis of BethesdaⅤnodule. The differences were present significantly in TI-RADS grade, aspect ratio and echo between Bethesda ⅤPTC group of 159 case and Bethesda Ⅵ thyroid nodule group of 251 cases (P<0.05). Further multivariate analysis showed that TI-RADS grade, aspect ratio, relation of nodule with capsule, thyroid peroxidase antibody level and echo were the risk factors for the diagnosis of PTC. Conclusions Bethesda Ⅴ nodules with higher grade of TI-RADS are malignant more possibly and those with lower grade of TI-RADS need to be evaluated such as thyroid nodules sizes, relation of nodules with capsule and thyroid peroxidase antibody level.